2011
DOI: 10.19030/jabr.v25i4.1016
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reputation And Earnings Quality

Abstract: <p class="MsoNoSpacing" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-family: &quot;Times New Roman&quot;,&quot;serif&quot;; font-size: 10pt;">Investor confidence and the quality of reported information are primary issues in our current financial reporting environment as a result of recent scandals and financial crises. Assessing the quality of reported financial information is an important issue for investors. Can investors use corporate reputation to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 19 publications
3
30
0
1
Order By: Relevance
“…These results add to other work that examines the relationship between reputation and financial F performance. This paper also extends the work of Luchs et al (2009) which established a positive relationship between reputation and the quality of reported performance. This paper explores the relationship between reputation and actual performance efficiency.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results add to other work that examines the relationship between reputation and financial F performance. This paper also extends the work of Luchs et al (2009) which established a positive relationship between reputation and the quality of reported performance. This paper explores the relationship between reputation and actual performance efficiency.…”
Section: Introductionsupporting
confidence: 74%
“…Research also views a good reputation as a unique asset to a firm. For example, Luchs et al (2009) find that reputation is positively associated with an improved quality of reported performance. We extend this recent work by exploring the relationship between reputation and actual performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, personality influences not only decision-making or accounting information quality, but also the internal environment that the CEO forms part of, which in this research is considered as the corporate reputation. Cao, Myers, and Omer (2012), Garrett, Hoitash, and Prawitt (2014), Gertsen, Van Riel, and Berens (2006), and Luchs et al (2009) found that corporate reputation positively influences accounting information quality. Thus, a strong reputation is expected to decrease earnings management and fraud.…”
Section: Contextualizationmentioning
confidence: 99%
“…Except for investor responsiveness to earnings, these dimensions and attributes are based on earnings management and fraud, in which there is honest or dishonest discretion when applying an accounting policy. Intentional manipulation reduces accounting information quality and adversely affects investor and analyst forecasts (Luchs, Stuebs, & Sun, 2009).…”
Section: Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation